Walk and listen: A multidimensional study on the soundscape of a University District - Ilaria Grecchi; Giorgia Guagliumi; Oscar Azzimonti; Igor Costarelli; Antonio Sibilia; Giovanni Brambilla; Fabio Angelini; Roberto Benocci; Giovanni Zambon; Valentina Zaffaroni-Caorsi (PLoS ONE, 2026)
Human perception of a surrounding environment comes from our senses. Among these, vision has been considered the most important but, nowadays, the hearing perception features are attracting even more the attention of researchers. This study, based on five soundwalks conducted in the university district of Milano-Bicocca, compared subjective emotional responses evoked by the soundscape with psychoacoustic parameters determined from binaural recordings. Furthermore, a focus group discussion conducted at the end of each soundwalk made it possible to explore participants’ in-depth perceptions and to collect their accounts of everyday life in the neighbourhood, their geographical backgrounds, and their habitual and preferred soundscapes. From the survey analysis, a consistent preference emerged for green areas, which were also statistically clustered based on psychoacoustic indices, as well as the squares and the two sites most exposed to traffic, indicating alignment between subjective responses and psychoacoustic structure. Moreover, sites with comparable A-weighted sound pressure levels (dBA) elicited different perceptual evaluations: environments featuring water sounds were systematically perceived as less noisy, while the sites with the highest dBA levels were perceived either as chaotic or monotonous, depending on the listener’s subjective interpretation and the perceived meaning of the dominant noise source. These results reinforce the hypothesis that sound perception is shaped by contextual and semantic factors, and cannot be fully captured by conventional acoustic metrics alone.